Influencia de la adición de ceniza de cáscara de arroz activada alcalinamente sobre la estabilización ecológica de la mezcla suelo - sedimento en la provincia de virú - Alvarado Ruiz, Cinthya Vanessa (2018)
In this research, the stabilization of sandy soils of the access roads to agricultural areas incorporated by the Chavimochic project was studied through the addition of clarification sediments of irrigation waters that optimize and increase their granulometric gradient and cohesion respectively, as well as the addition of ash rice husk (CCA) and limestone residue from scallop shells (RCCA) to improve its support capacity. The objective was to determine the influence of the addition of alkaline activated rice husk ash on the ecological stabilization of the soil sediment mixture for use on unpaved roads in the province of Virú. Soil and sediment were collected in the Chao district, department of La Libertad. The physical properties, chemical composition and phase analysis of the soil, sediment, CCA and RCCA were determined according to ASTM standards. The results of the Attemberg limits showed that the mixture 65% soil + 35% sediment shows better cohesion properties, in the same way the chemical analysis and phase tests revealed that the calcined RCCA contains 96.57% of CaO and the CCA possesses a 94.10% of SiO2 whose combination produces pozzolanic reactions similar to those that can be observed in cementing materials. We have determined the resistance, cohesion and plasticity that the soil acquired when it was mixed with sediment in the first instance, and then with CCA and RCCA. The processed specimens were cured for 7, 14 and / or 30 days and then subjected to the following geotechnical tests: Modified Proctor, CBR, Unconfined Compression and Triaxial Compression Test UU. Based on the experimental results, it was concluded that the mixture 65% soil + 35% sediment increases the CBR value from 5.1 (100% soil) to 31.0 and this is further improved to 144.70 when the previous mixture is added 8% CCA and 2% RCCA. Also, in these 2 cases an increase in the cohesion and the internal friction angle was verified, calculated from the intrinsic resistance lines, defined as the envelope of the Mohr circles in different tension states using the Terzagui equation. Finally, using the NAASRA method a rolling layer thickness of 20 cm was calculated. This proposal represents an ecological alternative that takes advantage of the sediments and industrial waste of the region to enable new access roads in an economic and sustainable manner